Géis de acetato de celulose reticulados: síntese, caracterização e estudos de adsorção de íons Cu+2 - Senna, André Martins (2011)
This paper reports the synthesis of gels derived from cellulose acetate, degree of substitution (DS) 2.5, through by esterification and crosslinking reactions between hydroxyl groups and acid dianhydride benzene- 1, 2, 4, 5-tetracarboxilic (PMDA). After the synthesis of gels, they carried out as substrates for adsorption of Cu+2. The characterizations were performed using the techniques: TGA Analysis spectroscopy infrared (FTIR), back titration to determine the degree of substitution (GS) of cellulose acetate and atomic force microscopy (AFM). The gels were synthesized with the stoichiometric following ratios (PMDA/OH): 1:1, 1:1.5, 1:3 and 3:1. Confirmation of the esterification reaction was possible by analysis of FTIR and TGA and confirmation of the adsorption of copper ions was possible through the analysis of TGA where it was observed by comparing the curves of the gels without copper ions adsorbed to the curves of the gels with copper ions adsorbed. Was obtained by an adsorption isotherm of copper ions based on the Langmuir model. The results of determination of cross-links through the theory of Flory-Rehner showed that the crosslink density was higher in the gel synthesized with excess PMDA and lower in the gel synthesized with 1 mol of PMDA stoichiometry: 3 mol of free OH.